Like Quicksand: Reflections on the Contribution of Care to the Educational Relationship - Dias, Dany (Journal of the Canadian Association for Curriculum Studies, 2023)
Even before the pandemic subjected us to new realities and different teaching and learning environments, anxiety, fatigue, feelings of powerlessness and hopelessness were felt. Like quicksand, these states of ill-being overwhelm learners in their academic momentum. This phenomenon is certainly not only a consequence of the pandemic. In my role as a teacher and now as a professor, I have seen it come out of the woodwork and amplify at an alarming rate. However, my role as an academic is shaped and reshaped in response to these observations. Noddings (2003) argues that caring relationships are ends in themselves, not simply means to achieve learning outcomes; the contribution of an ethic of care in the educational relationship between learner and teacher is important. Do our educational intentions about the curriculum remain too rigid? Does our teaching practice include the possibility of hearing stressed voices, anguished words, tormented hearts? Are we listening to the human condition in our learners? Although everything may seem fine, the anxiety is real, and it is our responsibility to address it. This article is the result of a pedagogical reflection, from the lens of an educator in the pandemic era.